Cyclodextrin-Promoted Fluorescence Detection of Aromatic Toxicants and Toxicant Metabolites in Commercial Milk Products - DiScenza, Dana J. (Food Anal Methods, 2018)
The detection of polycyclic aromatic hydrocarbons (PAHs) and their metabolites in food and in agricultural sources is an important research objective due to the PAHs’ known persistence, carcinogenicity, and toxicity. PAHs have been found in the milk of lactating cows, and in the leaves and stems of plants grown in PAH-contaminated areas, thereby making their way into both cow milk and plant milk alternatives. Reported herein is the rapid, sensitive, and selective detection of 10 PAHs and PAH metabolites in a variety of cow milks and plant milk alternatives using fluorescence energy transfer from the PAH to a high quantum yield fluorophore, combined with subsequent array-based statistical analyses of the fluorescence emission signals. This system operates with high sensitivity (low micromolar detection limits), selectivity (100% differentiation even between structurally similar analytes), and general applicability (for both unmodified lipophilic PAHs and highly polar oxidized PAH metabolites, as well as for different cow and plant milk samples). These promising results show significant potential to be translated into solid-state devices for the rapid, sensitive, and selective detection of PAHs and their metabolites in complex, commercial food products.